Validación de una Metodología de Clasificación de Imágenes Satelitales en un Entorno Orientado a Objetos - Ardila López, Juan Pablo; Espejo Valero, Oscar Javier; Herrera Escorcia, José Luis (Ingeniería, 2004)
This paper presents the results of the undergraduate thesis work, which aim was the introduction and comparison of a thematic information image extraction procedure based on an object oriented approach versus a traditional per pixel classification methodology. The document reviews theoretical concepts and the methodological implications of the shift towards and object oriented image classification process, in which the object is considered as the main block of image analysis contrary to the traditional pixel approach. The background of an object oriented classification process is introduced, hypothesis and experiments are described, results are reported and finally conclusions are presented from on a quantitativeand qualitative point of view.